DERMATITIS KONTAK AKIBAT KERJA PADA PENATA RAMBUT - Oslan, Shirley M.; Bratiartha, Made (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 R e ports f r om d e rm a to l o g is t , the r e is a n inc r ea sing r a te of o cc up a t ional c onta c t d e rm a t i t i s f r om y e a rs to y e a rs. O cc u p a t i on a l c onta c t d e rm a t i t i s , b a s e d on i t s p a thop h y sio l og y , ca n b e div i d e d in t o a l l e r g ic c onta c t d e rm a t i t i s a nd i r ritant c onta c t d e rm a t i t i s. Un f o r tuna t e ly both h a v e a si m i l a r c l i nic a l p re s e ntation th a t sometimes dif f icult to dif fe r e nt i a te, but a p rec ise di a g nosis is n ee d e d to g ive the most e f fec t i ve tr ea t m e nt. H a i rd re ss e rs p la ce d in the th i rd r a nk i n the most hi g h l y risk o cc up a t i on f o r o cc up a t i on a l c onta c t d e r mati t is. P rop e r identifi c a t i on on too l s a nd mat e ri a ls used in eac h o cc u p a t i on, method of wo r ki n g , a nd other ri s k f a c tors is n ee d e d in o r d e r to p r e v e nt o cc up a t i on a l con t ac t de r mati t is, for h a ird re ss e rs in p a rticul a r. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: occupational contact dermatitis, hairdressers, allergy, irritant.